2003
DOI: 10.1007/s00468-002-0240-0
|View full text |Cite
|
Sign up to set email alerts
|

Meristematic nodule culture: a new pathway for in vitro propagation of Eucalyptus globulus

Abstract: Morphogenesis was induced in Eucalyptus globulus seeds, cotyledons, hypocotyls and leaves from in vitro clonal plantlets. Globular structures were observed after 2 weeks induction on B5 culture medium supplemented with 10% coconut water, 0.05-0.5 mg l 1 6-benzylaminopurine (BAP) and 0.5 mg l 1 indole-3butyric acid (IBA). These continued to proliferate under dark conditions until the 2nd to 3rd subculture. Following transfer to a photoperiod of 16 h light, shoots evolved from these globular structures and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…To our knowledge, this is the first report of MNs culture system capable of de novo shoot organogenesis in tree peony. MNs have been identified in both direct (Piéron et al 1993(Piéron et al , 1998Trindade and Pais 2003;Ferreira et al 2009;Moyo et al 2009), and indirect morphogenesis pathways through an intervening callus phase (Aitken-Christie et al 1988;Batista et al 2000;Fortes and Pais 2000;Xie and Hong 2001). In our studies, the MNs was initiated indirectly form calli derived from cotyledons of P. ostii 'Feng Dan', which was consistent with previous descriptions in P. lemoinei 'Golden Era' (Qin et al 2012) and P. rockii (zhong 2011).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To our knowledge, this is the first report of MNs culture system capable of de novo shoot organogenesis in tree peony. MNs have been identified in both direct (Piéron et al 1993(Piéron et al , 1998Trindade and Pais 2003;Ferreira et al 2009;Moyo et al 2009), and indirect morphogenesis pathways through an intervening callus phase (Aitken-Christie et al 1988;Batista et al 2000;Fortes and Pais 2000;Xie and Hong 2001). In our studies, the MNs was initiated indirectly form calli derived from cotyledons of P. ostii 'Feng Dan', which was consistent with previous descriptions in P. lemoinei 'Golden Era' (Qin et al 2012) and P. rockii (zhong 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Simultaneously, mixed use of CKs presented better response than single one, which was in accordance to results in Garcinia mangostana (Te-chato and Lim 2000). However, studies on Eucalyptus globulus showed contradictory results, BA enhanced both nodule induction and shoot organogenesis, but in the presence of CPPU, explants showed vitrification and no morphogenesis (Trindade and Pais 2003). This might be attributed to the fact that CPPU was far beyond its requirement on CKs activity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to a study on tree peony 15 , the regeneration of Xanthosoma involved four distinct phases that included callus with multiple meristematic regions, pre- nodules, meristematic nodules and shoot primordia. Formation of meristematic nodules either directly or indirectly via callogenesis has been reported in a number of species including Acacia mangium 16 , Eucalyptus globulus 17 , Humulus lupulus 18 , 19 , Populus euphratica 20 , Sclerocarya birrea 21 etc. Analogous observations have been made in a study on Elliottia racemosa 22 , in which in vitro regeneration from leaf explants took place via shoot organogenesis on a medium containing TDZ and IAA.…”
Section: Resultsmentioning
confidence: 99%